Development of specific tests in bike-trials riders and relationship with jumping ability - Thomas, P.-C.; Miny, K.; Jidovtseff, B. (Science & Sports, 2018)
Aims of the study: The first aim of this study was to set a battery of field tests in order to assess specific muscular function of biketrial riders. The second aim was to investigate the discrimination of these tests by comparing the performance of elite and amateur riders. Material and method: Twenty ELITE biketrial riders and 13 biketrial amateurs (AMAT) underwent field tests. The battery of field tests consisted in four non specific jumping tests (SJ, CMJ, SBJ and Reactivity) and three original specific tests on the bike (bike gap, side-hop over an elastic and holding time on the back-wheel). All the tests were performed on the field with portable equipment. Results: The results show that bike specific tests are very discriminant: ELITE riders were significantly superior in each test (P<0.001) The 20in riders seem to have a greater jumping ability in comparison with the 24in riders. The correlation between the jumping field tests and the bike specific tests is fairly high (r>0.7). Conclusion: The field tests as well as the bike specific tests showed to be selective and discriminant for the biketrial rider's. Jumping ability appears to be very important in order to achieve the elite level.